Hypnotic Suggestions Given Before Nighttime Sleep Extend Slow-Wave Sleep as Compared to a Control Text in Highly Hypnotizable Subjects. Issue 1 (2nd January 2020) - Cordi, Maren Jasmin; Rossier, Laurent; Rasch, Björn
ABSTRACT: While slow-wave sleep (SWS) is fundamental for maintaining health and well-being, it is typically reduced with stress or age. The authors have previously reported that hypnotic suggestions before sleep increased SWS duration and slow-wave activity (SWA) during a midday nap in hypnotizable younger and older women. To test generalizability, they investigated this effect across 8 hours nighttime sleep in 43 healthy young French-speaking subjects (19 males) of high and low hypnotizability. In accordance with their previous results, listening to hypnotic suggestions before sleep was followed by higher amounts of SWS in highly hypnotizable subjects and higher SWA power compared to a control condition. The effects were most pronounced at the beginning of the night. Further studies are needed to examine whether hypnotic suggestions can deepen sleep also above non-intervention nights. The findings provide a basis for the examination and potential application of hypnosis to improve sleep in clinical populations.